Strategy for strengthening capacity of aparatur leadership through the capacity building training in DKI Jakarta - Farihah Sulasiah (Monas: Jurnal Inovasi Aparatur, 2019)
ASN is a driving element of an organization. Three competencies that must be possessed by an ASN, there are technical competencies, managerial competencies, and social-cultural competencies that need to be continuously developed as an effort to improve performance of ASN as a state apparatus. One of the efforts that was realized in the implementation of Capacity Building Education and. Change leaders are expected to have social sensitivity that is able to move the community and be resilient by aligning the power of the brain and heart through a wise approach (high touch). This ability is the collaboration of one's ability to manage information and knowledge by utilizing intuition, motivation and wisdom with a touch of entertainment. The implementation of the education and training program is unique in the material content and evaluation system. The implementation of CB training is aimed at challenging participants in solving various problems that occur in DKI through strategic thinking that hones organizational concerns and is equipped with group interaction. In this way participants are motivated to maximize inspirational and interpersonal motivation, intrapersonal skills by using a variety of innovative ideas in managing the changes seen in solving a given problem. This is in accordance with the demands of competence at Pergub 272/ 2014. This adapts several employee competencies that are regulated through local government regulations and supplemented by observation activities as a form of qualitative assessment of participants. This study uses a qualitative approach with descriptive methods based on events that have already occurred. This method provides an in-depth overview of the problems observed. Observations were made on the implementation of capacity building training which was carried out for three days in three consecutive forces. The research instrument is the researcher himself.